Pembelajaran Model Blended Learning - Husni Idris (Jurnal Ilmiah Iqra', 2011)
A blended approach to a traditional, face to face course might mean that the class meets once per week instead of the usual three-session format. Learning activities that otherwise would have taken place during classroom time can be moved online. In addition, the terms "blended," "hybrid," and "mixed mode" are used interchangeably in current research literature.Keyword: blended, learning, face to face, online and offline.